Switching from originator adalimumab to biosimilar SB5 in a rheumatology cohort: persistence on treatment, predictors of drug interruption and safety analysis. (July 2021) - Bruni, Cosimo; Gentileschi, Stefano; Pacini, Giovanni; Bardelli, Marco; Tofani, Lorenzo; Bartoli, Francesca; Baldi, Caterina; Cometi, Laura; Fiori, Ginevra; Nacci, Francesca; Cantarini, Luca; Guiducci, Serena; et al.
Aims: Medical and non-medical switching strategies have been adopted in Europe in the last few years. We aimed to investigate persistence on treatment with a SB5 Adalimumab (SB5) biosimilar after switching from Adalimumab (ADA) originator among patients with inflammatory rheumatic musculoskeletal diseases (iRMD), identifying possible predictors of drug interruption and describing adverse events. Method: iRMD patients previously switched to SB5 after at least 6 months of ADA were enrolled. Data on concomitant medications, disease flares, and persistence on SB5 up to the last available follow up were collected retrospectively. Kaplan–Meier and Cox regression models were used. Result: A total of 172 patients (106 females, ADA duration 5.8 ± 3.8 years) were enrolled, including 34 rheumatoid arthritis, 59 psoriatic arthritis, and 61 axial spondyloarthritis patients. In a 10 ± 3 months follow up, 65 (37.8%) patients presented with adverse events, with 46 (26.7%) showing a clinically defined disease flare (no disease activity and patient reported outcomes assessment were available); 24 patients interrupted SB5 permanently (among them, 11 back-switched to ADA and 8 were prescribed a different biological therapy). Probability of persistence on SB5 was 94.7% at 6 months and 85.1% at 12 months. Baseline corticosteroid [hazard ratio (HR) 3.209, 95% confidence interval (CI) 1.193–8.635, p  = 0.021] and therapy with nonsteroidal anti-inflammatory drugs (NSAIDs) (HR 2.876, 95% CI 1.229–6.727, p  = 0.015), as well as the baseline corticosteroid dose (HR 1.200, 95%CI 1.026–1.403, p  = 0.022) were predictors of drug interruption. Conclusion: Our data on persistence of treatment and adverse events are in line with previous reports. Further large cohort studies may confirm baseline corticosteroid and NSAIDs use as predictors of SB5 interruption, helping to identify patients at higher risk of failure after switching.